2006
DOI: 10.7326/0003-4819-144-3-200602070-00004
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Pulmonary Embolism in the Emergency Department: The Revised Geneva Score

Abstract: The proposed score is entirely standardized and is based on clinical variables. It has sustained internal and external validation and should now be tested for clinical usefulness in an outcome study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
306
8
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 875 publications
(354 citation statements)
references
References 22 publications
9
306
8
4
Order By: Relevance
“…This uses a number of clinical features in a structured manner to generate an estimate of the clinical risk of PE or a rule to determine whether or not PE should be investigated. In the general (non-pregnant) population with suspected PE, Wells'sscore 3 and revised Geneva score 4 have been developed to estimate the risk of developing PE, whereas the PE rule-out criteria (PERC) rule 5 has been developed to select patients for investigation (details of the scores and the rule are provided in Chapter 3). These scores and the rule have been extensively validated in the general population with a suspected PE, but the differences between the pregnant and non-pregnant populations mean that findings cannot be automatically extrapolated to the pregnant or postpartum population.…”
Section: Background and Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…This uses a number of clinical features in a structured manner to generate an estimate of the clinical risk of PE or a rule to determine whether or not PE should be investigated. In the general (non-pregnant) population with suspected PE, Wells'sscore 3 and revised Geneva score 4 have been developed to estimate the risk of developing PE, whereas the PE rule-out criteria (PERC) rule 5 has been developed to select patients for investigation (details of the scores and the rule are provided in Chapter 3). These scores and the rule have been extensively validated in the general population with a suspected PE, but the differences between the pregnant and non-pregnant populations mean that findings cannot be automatically extrapolated to the pregnant or postpartum population.…”
Section: Background and Rationalementioning
confidence: 99%
“…4 These rules were not developed for use in the pregnant population, so we removed criteria that were not relevant to the pregnant population and adapted criteria when appropriate to be relevant to the pregnant population. We therefore removed exogenous oestrogen from the PERC rule and used the thresholds developed for our analysis of clinical variables to dichotomise age, oxygen saturation and heart rate (see Table 4).…”
Section: Case-control Studymentioning
confidence: 99%
“…The Wells criteria consist of six objective variables and one subjective variable which requires physician assessment regarding the chance of a diagnosis, other than PE, for the patient's condition (Table 1) (17). Conversely, the more recently revised Geneva score incorporates eight objective clinical variables (12).…”
Section: Discussionmentioning
confidence: 99%
“…However, in order to eliminate this restriction, the Geneva group created and verified a com- pletely standardized objective rule called the Geneva score revised later. It has been recently simplified into the simplified revised Geneva score (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 To promote appropriate use of resources, several groups have validated clinical prediction rules to guide clinicians to either test further or exclude PE as a potential diagnosis. [3][4][5][6][7][8] However, a survey of emergency clinicians demonstrated that many use implicit, nonvalidated criteria when formulating a pretest probability. 9 The goal of this study was to determine the association of validated (explicit) and nonvalidated (implicit) criteria with the diagnosis of PE.…”
Section: Introductionmentioning
confidence: 99%